2021
DOI: 10.1002/mc.23335
|View full text |Cite
|
Sign up to set email alerts
|

Benzo[a]pyrene diol epoxide‐induced transformed cells identify the significance of hsa_circ_0051488, a ERCC1‐derived circular RNA in pulmonary squamous cell carcinoma

Abstract: ERCC1 is a gene for repairing DNA damage whose function is related to carcinogenic‐induced tumorigenesis and the effectiveness of platinum therapies. Circular RNAs (circRNAs) are products of posttranscriptional regulation with pleiotropic effects on the pathogenesis of lung cancer. We aim to identify that specific circRNAs derived from ERCC1 can regulate key biological processes involved in the development of lung cancer. We performed bioinformatics analysis, in vitro experiments, and analyzed clinical samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…In this study, we performed differential expression analysis on the GSE164803 dataset in the GEO database, identified seven circRNAs with significantly upregulated expression in liver cancer tissues compared with normal liver tissues and verified them in LIHC clinical specimens by qRT–PCR. Among them, one circRNA was previously reported to be closely related to cancer: hsa_circ_0051488 sponges miR-6717–5p, thereby regulating the expression of SATB2, which plays a vital role in lung squamous cell carcinoma ( Xiao et al, 2021 ). However, there is no research focusing on the significance of the other circRNAs, and they are worthy of further study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we performed differential expression analysis on the GSE164803 dataset in the GEO database, identified seven circRNAs with significantly upregulated expression in liver cancer tissues compared with normal liver tissues and verified them in LIHC clinical specimens by qRT–PCR. Among them, one circRNA was previously reported to be closely related to cancer: hsa_circ_0051488 sponges miR-6717–5p, thereby regulating the expression of SATB2, which plays a vital role in lung squamous cell carcinoma ( Xiao et al, 2021 ). However, there is no research focusing on the significance of the other circRNAs, and they are worthy of further study.…”
Section: Discussionmentioning
confidence: 99%
“…A xenograft tumor growth assay suggested that it acted as a tumor promoter in LUSC and influenced LUSC proliferation and invasion via the miR-136-5p/Rho associated coiled-coil containing protein kinase 1 (ROCK1) axis ( 87 ). In addition, hsa_circ_0051488 expression in cancer tissues was inversely correlated with tumor diameter, lymphatic metastasis and TNM stage ( 88 ). Further experiments indicated that circ0051488 may promote LUSC progression through the miR6715/special AT-rich sequence-binding protein 2 (SATB2) axis, suggesting that circ0051488/miR6715/SATB2 may be a potential pathway for LUSC therapeutic intervention ( 88 ).…”
Section: Characteristic Circrnas In the Progression Of Different Type...mentioning
confidence: 99%
“…In addition, hsa_circ_0051488 expression in cancer tissues was inversely correlated with tumor diameter, lymphatic metastasis and TNM stage ( 88 ). Further experiments indicated that circ0051488 may promote LUSC progression through the miR6715/special AT-rich sequence-binding protein 2 (SATB2) axis, suggesting that circ0051488/miR6715/SATB2 may be a potential pathway for LUSC therapeutic intervention ( 88 ).…”
Section: Characteristic Circrnas In the Progression Of Different Type...mentioning
confidence: 99%